Z Specification of Gate and Apron Control Management at Airport - Nazir Ahmad Zafar; Fahad Alhumaidan; Sher Afzal Khan (Abstract and Applied Analysis)
Modelling of an air traffic control (ATC) system is an open issue and has become a challenging problem due to its complexity and increase of traffic at airports and in airspace. Consequently, automated ATC systems are suggested to improve efficiency ensuring the safety standards. It is reported that the number of collisions that occurred at airports surface is three times larger than in airspace. Further, it is observed that gates and aprons congestions cause significant delays at airports; hence, effective monitoring and guidance mechanisms are required to control ground air traffic. In this paper, formal procedure of managing air traffic from gate to enter in the active area of airport for taxiing is provided using Z notation. An integration of gate and apron controllers is described to manipulate the information for correct decision making and flow management. Graph theory is used for representation of airport topology and appropriate routs. In static part of the model, safety properties are described in terms of invariants over the critical data types. In dynamic model, the state space is updated by defining pre- and postconditions ensuring the safety. Formal specification is analysed using Z/Eves tool.